"I Have Been Trying to Get Them to Respond to Me": Sexuality and Agency in Psychoanalysis. Issue 1 (2nd January 2016) - Slavin, Jonathan H.
Abstract: Psychoanalytic theory has seen many changes in the past 100 years. But in the process, sexuality, as the centerpiece of our understanding of human motivation and conflict, seems to have gotten lost. As they did a century ago, clinicians today deal with sexual transferences and countertransferences. And issues of gender and sexual orientation are widely discussed. Yet, across most current theoretical perspectives, nothing compels us to focus on sexuality, as such, in the way that was once absolutely essential. During the same period, psychoanalytic approaches have consistently been concerned with questions of personal agency, i.e., its disruption in development and restoration in treatment. Indeed, the aim of treatment was traditionally understood as enabling patients to repossess their experience of themselves as "agents" in relation to their own disowned motives, affects, and drives ("where id was, there shall ego be"). In contemporary interpersonal, intersubjective, and relational perspectives, the issue of agency takes on even more central significance. This article explores how these two seemingly different conceptual and developmental frameworks—sexuality as a function of mind, and agency as a derivative of relational experience—may be compatible. Here, I examine the relationship of sexuality and the experience of agency in parent–child and analyst–patient relationships, and suggest that sexuality as such may yet have a central role in contemporary psychoanalytic thinking and in our understanding of the basic nature of psychic functioning.